Fraud Detection in the Government Sector (An Empirical Study on the Audit Board of the Republic of Indonesia) - Ginting, Noya Andiana; Koeswayo, Poppy Sofia; Sukmadilaga, Citra (E-Jurnal Akuntansi; Vol 35 No 4 (2025)DO - 10.24843/EJA.2025.v35.i04.p15, 2025)
This study aims to analyze the influence of auditor professionalism and independence on fraud detection at the Audit Board of the Republic of Indonesia (BPK RI). This quantitative research collected data through questionnaires distributed to 125 auditors. Data analysis was conducted using multiple linear regression. The results indicate that auditor professionalism and independence positively and significantly influence fraud detection. This study provides practical contributions to developing fraud detection strategies in the public sector by emphasizing the importance of professional training and strengthening auditor independence. Keywords: Auditor professionalism; Auditor independence; Fraud detection; Public sector